Analysis of reliability and agreement of the methods caliper and fingerbreadths to measure the rectus abdominis diastasis - Pitangui, Ana Carolina Rodarti; Fukagawa, Letícia Kazue; Barbosa, Carla Santos; Lima, Alaine Souza; Gomes, Mayra Ruana de Alencar; Araújo, Rodrigo Cappato de (ABCS Health Sciences, 2016)
Introduction: Palpatory methods such as caliper and fingerbreadths are clinically viable techniques to determine the rectus abdominis diastasis. Objective: To evaluate the reliability and agreement of the fingerbreadths and caliper methods on measuring the rectus abdominis diastasis in the immediate postpartum. Methods: A descriptive crosssectional study with immediate postpartum women. The measurements were performed at different times by two evaluators. The reference points for measurement were: three fingers (4.5 cm) above and below the umbilicus region and at the umbilicus. The diastasis was scored by the caliper and by the number of fingers between the medial edges of the rectus abdominal muscles. A value of 1.5 cm was estimated for each finger. The diastasis was considered present when a distance greater than 3 cm occurred between the medial edges of the rectus abdominal. Statistical analysis was performed using weighted Kappa coefficient, to assess the agreement between the techniques, and intra-class correlation coefficient to assess reliability. In all analyses, a significance level of p<0.05 was adopted. Results: A total of 261 postpartum women were evaluated, with mean age of 23.74±6.42 years. Of these, 143 (54.8%) were primiparous and 118 (45.2%) were multiparous. Excellent values of reliability were verified in the fingerbreadths technique and moderated ones were observed with the use of caliper. The agreement between the two techniques demonstrated to be excellent. Conclusion: Both techniques, fingerbreadths and caliper, have proven to be reliable instruments with agreement in measuring the rectus abdominis diastasis.